2000
DOI: 10.1074/jbc.m003237200
|View full text |Cite
|
Sign up to set email alerts
|

SNAP-25 Functional Domains in SNARE Core Complex Assembly and Glutamate Release of Cerebellar Granule Cells

Abstract: Synaptosomal associated protein of 25 kDa (SNAP-25) is a member of the SNARE protein complex that has been implicated in synaptic vesicle docking and fusion. In this report, we have generated SNAP-25 mutants and assayed their functions in SNARE complex formation and glutamate release from cultured rat cerebellar granule cells. In vitro binding studies show that a deletion mutant lacking the C-terminal 181-206 amino acid sequence inhibits the formation of the SNARE core complex. Additional deletion of an N-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…In addition, our binding data demonstrate that the C-terminal deletion mutant unlike wild type SNAP-25 was relatively ineffective in associating with syntaxin-1. These secretion and binding data agree with a previous study involving cerebellar neurons, which showed that overexpressed SNAP-25 ⌬180 -206 mutant altered the vesicle fusion kinetics, reaffirming the importance of SNAP-25 and specifically this C-terminal segment in exocytosis (12). The results also add further evidence for the importance of SNARE proteins for the activation of parietal cells.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In addition, our binding data demonstrate that the C-terminal deletion mutant unlike wild type SNAP-25 was relatively ineffective in associating with syntaxin-1. These secretion and binding data agree with a previous study involving cerebellar neurons, which showed that overexpressed SNAP-25 ⌬180 -206 mutant altered the vesicle fusion kinetics, reaffirming the importance of SNAP-25 and specifically this C-terminal segment in exocytosis (12). The results also add further evidence for the importance of SNARE proteins for the activation of parietal cells.…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that SNAP-25 may promote membrane fusion by contributing two cytoplasmic-helices including the C-terminal helix to stabilize the four-helix core complex. Yang et al (12) recently report that the overexpression of the C-terminal deletion mutant ⌬180 -206 significantly inhibited glutamate release from neuronal cells. Because of the functional effects in neuronal cells, we used the C-terminal deletion mutant to study the function of SNAP-25 in parietal cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibitory effect of GST-SNAP-23del1-203 on PC Ig secretion is consistent with the results observed in 3T3-L1 adipocytes infected with recombinant adenoviruses carrying SNAP-23delC8 (48). The explanation of how GST-SNAP-23delC8 inhibits cell secretion remains unknown, but it has been suggested that a competition could exist between the deleted protein and the endogenous SNAP-23, resulting in either the formation of unstable SNARE complexes of GST-SNAP-23delC8 with the other SNARE partners (49,50), or the prevention of endogenous SNAP-23 from forming a SNARE complex (51). The finding that undeleted GST-SNAP-23 also produces an identical inhibition of PC Ig secretion indicates that additional events might explain the present results.…”
Section: Discussionmentioning
confidence: 95%